(3OQGSGJ aj GdjghOjI hGdeSjMjI hCOjGf GdgfO (B/s - (3GdCYXei, eMeO VjGA GdQMefs (Riyad : Maktabah al-Rushd, 2001)
Judaism; Christianity; religions and mythology of India; history; Islamic interpretations
Keywords: Judaism; Christianity; Hinduism; Buddhism; Religions; India -- Religion